The mediating effect of subject well-being between physical activity and the internet addiction of college students in China during the COVID-19 pandemic: a cross-sectional study - Wang, Jinfu; Xu, Xue; Wu, Qinmei; Zhou, Chao; Yang, Guan (Frontiers in Public Health, 2024)
Background Internet addiction poses a significant threat to the health of college students worldwide, but physical activity, as a highly safe and effective rehabilitative measure, has shown promise for alleviating this issue nowadays. However, during the COVID-19 pandemic, the mediating processes in this association remained unclear. This study aims to explore the impact of physical activity on internet addiction among college students and the mediating role of subjective well-being. Methods A survey was conducted on 216 eligible college students using the physical activity level scale, the internet addiction test, and the subjective well-being scale. For data analysis, independent sample t-tests, correlation analysis, hierarchical regression analysis, and mediating effect tests were in turn carried out in this work. Results The study revealed noteworthy gender disparities in physical activity and internet addiction among college students (β = −0.356, p < 0.01; β = 0.140, p < 0.05). Compared to females, male students manifest elevated levels of physical activity and lower scores in internet addiction. Physical activity and subjective well-being exerted a significantly negative predictive influence on internet addiction (β = −0.162, p < 0.05; β = −0.508, p < 0.001). What’s more, subjective well-being assumed a crucial mediating role in the relationship between physical activity and internet addiction, with the mediating effect accounting for 72.81% of the total effect. Conclusion This study deepens the understanding of how physical activity reduces internet addiction risk while emphasizing that enhancing subjective well-being is an effective strategy for college students to cope with Internet addiction.